Effectiveness of tolterodine in relief of postoperative symptoms related to urethral catheter in transurethral prostate resection patients: a prospective randomized trial - Afandiyev, Faraj; Gökçe, Mehmet Ilker; Özcan, Cihat; İbrahimov, Anar and Gülpinar, Ömer (International Surgery Journal, 2020)
Background: Urethral catheterisation following surgery causes significant discomfort postoperatively. Use of muscarinic receptor antagonists for relief of these symptoms in transurethral prostate resection (TURP) patients has been studied previously. In this study it is aimed to identify efficacy of toltoredine for relief of bladder overactivity symptoms in the post-operative period following TURP. Methods: In this randomized, prospective, controlled study, results of 95 patients evaluated. Group 1(n=49) received tolterodine 4 mg/day and group 2 (n=45) received no medication. Presence and severity of symptoms together with visual pain scale (VPS) scores were recorded and compared in very early and late postoperative period (0, 4, 8, 12, 24 hours and every 24 hours thereafter). Additional analgesic requirement was also compared and adverse events were recorded. Results: Tolerodine treatment was shown to be associated with low incidence and less severity of symptoms. Symptoms were shown to be present especially in the early postoperative period. VPS scores were also shown to be less in group 1. Treatment was not cessated in any of the patients due to adverse events. Conclusions: Tolterodine 4 mg/day was shown to be effective in relief of symptoms related to urethral catheterisation in the postoperative period following TURP. Treatment was not cessated in any of the patients due to adverse events. Further prospective placebo-controlled studies are needed with tolterodine and other muscarinic receptor antagonists.